2017
DOI: 10.1177/2309499017692705
|View full text |Cite
|
Sign up to set email alerts
|

Early results of patellofemoral inlay resurfacing arthroplasty using the HemiCap Wave prosthesis

Abstract: Background: Common surgical treatment options for isolated patellofemoral osteoarthritis include arthroscopic procedures, total knee replacement and patellofemoral replacement. The HemiCap Wave patellofemoral resurfacing prosthesis is a novel inlay design introduced in 2009 with scarce published data on its functional outcomes. We aim to prospectively evaluate early functional outcomes and complications, for patients undergoing a novel inlay resurfacing arthroplasty for isolated patellofemoral arthrosis in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Ten papers met the criteria that we had posed: four of them (40%) dealt with the HemiCAP focal femoral condyle resurfacing prosthesis, 3 , 14 , 17 , 18 four (40%) explored the clinical use of the HemiCAP-Wave® implant for the treatment of trochlear cartilage lesions, 15-21 one study (10%) dealt with both these implants (HemiCAP focal and HemiCAP-Wave® implant) 16 and one study (10%) with the UniCAP implant for femoral condyle cartilage defects ( Table 1 ). 13-21 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ten papers met the criteria that we had posed: four of them (40%) dealt with the HemiCAP focal femoral condyle resurfacing prosthesis, 3 , 14 , 17 , 18 four (40%) explored the clinical use of the HemiCAP-Wave® implant for the treatment of trochlear cartilage lesions, 15-21 one study (10%) dealt with both these implants (HemiCAP focal and HemiCAP-Wave® implant) 16 and one study (10%) with the UniCAP implant for femoral condyle cartilage defects ( Table 1 ). 13-21 …”
Section: Resultsmentioning
confidence: 99%
“…In the current review, we found 5 clinical trials which investigated the HemiCap ® Wave prosthesis. 15-21 The total number of patients involved were 154. The mean follow- up ranged from two years to seven years, while the complications’ rate was 9.7% (15 patients).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations